2015
DOI: 10.1097/rct.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability Investigation of Reduced Field-of-View Diffusion-Weighted Magnetic Resonance Imaging on Thyroid Glands

Abstract: Objective To investigate the repeatability of the quantitative magnetic resonance imaging (MRI) metric (apparent diffusion coefficient (ADC)) derived from reduced field-of-view diffusion-weighted (rFOV DWI) on thyroid glands in a clinical setting. Materials and Methods Ten healthy human volunteers were enrolled in MRI studies performed on a 3T MRI scanner. Each volunteer was designed to undergo 3 longitudinal exams (2 weeks apart) with 2 repetitive sessions within each exam, which included rFOV and conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 27 publications
6
32
1
Order By: Relevance
“…There have been very few studies published in the literature (11,23) using rFOV-DWI in the head and neck region, and those that exist were based on images acquired from a small number of volunteers, while investigations are still lacking in patients with head and neck clinical pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…There have been very few studies published in the literature (11,23) using rFOV-DWI in the head and neck region, and those that exist were based on images acquired from a small number of volunteers, while investigations are still lacking in patients with head and neck clinical pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…Riffel et al also reported that the ADC values of the pancreas were not significantly different between the two DWI methods. However, Lu et al discovered that the mean ADC values of thyroid glands based on the rFOV DWI sequence were significantly reduced compared with the values calculated based on the fFOV DWI sequence. Vidiri et al also reported that the mean ADC values of head and neck tumors were significantly different between DWI sequences.…”
Section: Discussionmentioning
confidence: 98%
“…Vidiri et al also reported that the mean ADC values of head and neck tumors were significantly different between DWI sequences. The reasons for the above ADC measurement disparities potentially include different physiologies of the investigated organs and the characteristic features of the rFOV DWI sequence in terms of artifact reduction, excellent fat saturation, and high resolution . In addition, the ADC value is influenced by numerous factors, such as the magnetic field strength, sequence protocols used, and b values .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] However, for patients with disseminate diseases, a reduced FOV cannot fulfill the clinical need for whole pelvic evaluation. Moreover, the mean tumor ADC obtained with zoomed EPI is not stable [23][24][25].…”
Section: Discussionmentioning
confidence: 91%